APPLICATION OF CANTABRIAN AND BINDER DRAINAGE TESTS IN DESIGNING OF POROUS ASPHALT BINDER CONTENT - Hardiman . (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2004)
Abstract Traditional mix design methods which normally incorporate the Marshall test are not appropriate to design porous asphalt because of the insensitivity of the Marshall stability values to variations in binder content. It is therefore appropriate specify the design binder content (DBC) for porous asphalt rather than the optimum binder content. The design binder content incorporates an upper and a lower limit. The lower limit of the DBC can be dictated by requirements to resist disintegration while the upper limit is specified to limit binder drainage yet maintaining a porous structure that would promote permeability. This paper presents the results of a laboratory investigation to determine design binder content for porous asphalt. Three gradations were tested each made up of 10, 14 and 20 mm maximum aggregate size. Two types binder was used, conventional 60/70 pen bitumen, and styrene butadiene styrene (SBS) modified bitumen. Based on the drainage test, target binder content as the upper limit content for SBS is higher than the base bitumen 60/70. These values will be lower when the maximum aggregate size is increased. Generally, the abrasion loss decreases as the binder content increases while the curve slopes downward and becomes flatter when a certain percentage of bitumen is exceeded. It was found that design binder contents corresponding to 10, 14 and 20 mm maximum aggregate size equal 5.4%, 5.0% and 4.5% respectively for conventional binder and 5.7%, 5.2% and 4.6% for SBS binder. However, the DBC content for SBS is higher from conventional binder.Key words: porous asphalt, binder drainage, cantabrian, design binder content